India Strive to Provide Universal Health Coverage - Gupta, Arti; Lohiya, Ayush; B, Venkatashiva Reddy (Journal of Pharmacy Practice and Community Medicine)
Background: Universal health coverage is the reflection of the political commitment of countries towards health. This paper reviews the functioning and progress of India compared to World towards universal health coverage and identifies the bottlenecks. Methods: We searched the following electronic databases: PUBMED, BMJ, LANCET, WHO Website, Unicef Website and Google Scholar for studies related to universal health coverage. All databases were searched form inception. In addition, we checked reference lists of reviews and retrieved articles for additional studies. From the searches, we reviewed the title and abstract of each paper and retrieved potentially relevant references. Results: The poor universal health coverage was observed in Africa, Asia, and Middle East. Among south Asian countries, Bangladesh had 0.4%, India 5.7%, Nepal 0.1%, Pakistan 0%, and Sri Lanka 0.1% universal health coverage respectively. The countries like Canada, Tunisia, Egypt, Libya, Korea, Thailand, Japan, Turkey and Yemen enabled success in the path towards UHC. India have one of the highest proportions of household out-of pocket expenditures on health in the world, estimated at 71.1% in 2008–09. Any form of social or voluntary health insurance covers merely 10% of the Indian population. Community-based health insurance schemes for less than 1% of the population. Conclusion: Major challenges to achieve universal health coverage in developing countries are the limited resources. The only way to reduce dependence on direct payments is for governments to encourage payments made in advance of an illness.
Keywords: Universal; Health; Care; Scheme; Program; Coverage